The importance of enteral nutrition to prevent or treat undernutrition in children undergoing treatment for cancer. (2nd July 2020) - Trehan, Amita; Viani, Karina; da Cruz, Luciane Beitler; Sagastizado, Stephany Zelaya; Ladas, Elena J.
Abstract: Nutrition therapy is a therapeutic approach to treating medical conditions and symptoms via diet, which can be done by oral, enteral or parenteral routes. It is desirable to include nutritional interventions as a standard of care in pediatric cancer units (PCUs) at all levels of care. The interventions are dependent on available resources and personnel across all clinical settings. Enteral nutrition is easy, inexpensive, uses the gastrointestinal tract, maintains gut mucosal integrity, and allows for individualized nutritional strategies. This narrative review describes enteral nutritional interventions for children undergoing cancer treatment and is aimed at PCUs of all levels of care located in a low‐ and middle‐income country.